A systematic approach to the development and validation process of a research tool: an overview - Phalswal, Uma; Kalia, Raman (International Journal Of Community Medicine And Public Health, 2026)
Research tool development and validation process is enigmatic and opaque due to the diverse range of techniques it requires. As a result, the main goal of this article is to provide an overview of the research tool development process as simply as possible in order to support the development of new, valid, and reliable research tools, as well as improvement of existing ones. We accomplish this work by presenting all of the required steps in the right sequence to develop a research tool. In light of our search, we suggest five phases of tool development and validation, each with its own sub-steps. The first step involves preparing the preliminary draft, which includes conceptualizing the construct, evaluating current practices, conducting focus group discussions, and creating the item pool. The second phase includes the tool draft's validation with internal and external review, as well as the tool's pre-testing. Phase three includes field testing of the finalized tool draft, sampling planning, and data collection. The fourth phase includes the analysis of research tool data with item analysis, exploratory factor analysis, internal consistency, and test-retest reliability. The fifth phase is all about scale interpretation using percentiles, standard scores, norms, and cut-off points. Additionally, we briefly discussed the key best practices indicated in each step. This review will help both scientists and practitioners to understand all the steps and methodologies of research tool development and validation.